ФУҚАРОЛИК ЖАМИЯТИГА ЎТИШ ШАРОИТИДА ОИЛАВИЙ ҚАДРИЯТЛАРНИНГ ЎРНИ (Scientific journal of the Fergana State University, 2023)
In this article conducted a scientific analysis of the role of family values in the transition to civil society in Uzbekistan.